Extended Reality for the Clinical, Affective, and Social Neurosciences - Thomas D. Parsons; Andrea Gaggioli; Giuseppe Riva (Brain Sciences, 2020)
Brain science research often involves the use of low-dimensional tools and stimuli that lack several of the potentially valuable features of everyday activities and interactions. Although this research has provided important information about cognitive, affective, and social processes for both clinical and nonclinical populations, there is growing interest in high-dimensional simulations that extend reality. These high-dimensional simulations involve dynamic stimuli presented serially or concurrently to permit the assessment and training of perceivers’ integrative processes over time. Moreover, high-dimensional simulation platforms can contextually restrain interpretations of cues about a target’s internal states. Extended reality environments extend assessment and training platforms that balance experimental control with emotionally engaging background narratives aimed at extending the affective experience and social interactions. Herein, we highlight the promise of extended reality platforms for greater ecological validity in the clinical, affective, and social neurosciences.